Konstruksi Simbolik Mubaligh Pop pada Film Sang Pencerah - Ridwan Rustandi; Andri Hendrawan (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2022)
The purpose of this study is to analyze the symbolic construction of the popular preacher in the film Sang Enlightenment. The research was conducted with a qualitative approach through media text analysis. Referring to Roland Barthes' semiotic analysis method, two stages are used to examine the symbolic identity of the preacher in this film. Namely, the significance of the first stage (denotation), which takes place through various scenes and dialogues of the actors, and the significance of the second stage (connotation), which reveals a particular meaning from the highlighted symbol or sign. Data were collected through observation and documentation. The results show two symbolic identities of the preacher in the film, namely the role identity as a modernist, critical, and wise preacher, and the social identity as a religious preacher who is faqih, mujadid, and progressive. This research has implications for strengthening digital da'wah studies, especially in strengthening the identity of popular preachers.